2022
DOI: 10.29226/tr1001.2022.292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monetary Policy on the Performance of Deposit Money Banks in Nigeria

Abstract: This study broadly seeks to analyze the effect of monetary policy on the performance of deposit money banks in Nigeria. This research was based on secondary source of data extracted out from Central Bank of Nigeria (CBN) statistical bulletin and Index mundi. The Autoregressive Distributed Lag (ARDL) approach to cointegration was applied to achieve the objective. The empirical results revealed that both in the long run and short run, bank lending rate (BLR) has been found to have a significant positive impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Logically, these relationships affirmed the descriptive statistics in table 4.1 where the average lending rate was 16.8% and the average deposit rate was 5.4%, thus the interest rate spread was 11.4%. This finding corresponds to the studies that found a significant positive relationship between the lending rate and bank performance (Otiwu, 2022;Bala, Godiya, Hadith, & Maijama'a, 2022); a significant and negative relationship between deposit rate and bank performance (Brown, 2020;Caliskan & Lecuna, 2020). Table 4.6 further indicates that loan-todeposit ratio is positively related to the performance at 5% level.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…Logically, these relationships affirmed the descriptive statistics in table 4.1 where the average lending rate was 16.8% and the average deposit rate was 5.4%, thus the interest rate spread was 11.4%. This finding corresponds to the studies that found a significant positive relationship between the lending rate and bank performance (Otiwu, 2022;Bala, Godiya, Hadith, & Maijama'a, 2022); a significant and negative relationship between deposit rate and bank performance (Brown, 2020;Caliskan & Lecuna, 2020). Table 4.6 further indicates that loan-todeposit ratio is positively related to the performance at 5% level.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The empirical review related to this study was mostly on Nigeria and is more on the effect of monetary policy on bank lending Modugu and Dempere (2022), Bala, Godiya, Hadith, and Maijama'a (2022), Adetutu et al, (2021), Olofinlade and Azeez (2021) Yunusa, Williams, and Adegbenle (2020), Lartey (2018), Abere, Obarafo, and Adewole (2020) Mukolu and Adeleke (2020), Olofinlade, Oloyede, and Oke (2020) and Mordi, et al (2019). Also, on the effect on bank credit especially to the private sector Awoniyi and Ogundipe (2021) 2018) Oyeyemi (2019).…”
Section: Empirical Reviewmentioning
confidence: 99%